The development of quantum cascade lasers - Chew, Brandon Yu (Nanyang Technological University, 2024)
Quantum Cascade Lasers (QCLs) have emerged as a groundbreaking technology with diverse applications across various fields, ranging from spectroscopy and gas sensing to telecommunications and imaging. This paper presents an overview of the fundamental principles, design considerations, and recent advancements in QCL technology. Beginning with an introduction to the underlying quantum mechanics principles governing QCL operation, we delve into the unique structural design features that enable efficient photon emission and amplification. Key topics such as band structure engineering, intersubband transitions, and waveguide design are explored in detail to understand how they impact QCL performance.